Microbites dinosaurs : riveting reads for curious kids - Dixon, Dougal (DK Publishing, 2020)
Furnishes historical information about dinosaurs, including when they lived, how fossils form, what is known and unknown about dinosaurs, what happened to the dinosaurs, and why information about them keeps changing. Includes a list of dinosaurs, discovery milestones, a dinosaur family tree, additional resources, a glossary, and an index.